Preparation and characterization of debranched starches: Influence of botanical source and debranching time. (1st May 2023) - Wang, Deda; Zheng, Xiaoqing; Liu, Wenhui; Sun, Qingjie; Chen, Hai-Hua; Mu, Hongyan
Graphical abstract: Highlights: Debranched starches (DBSs) from four kind of botanical sources were prepared via pullulanase hydrolysis. The morphology and granular size of native starches affected the preparation of DBSs. Physicochemical properties of DBS were greatly impacted by the debranching time. Level of digestive fractions was related with both botanical source and debranching time. Abstract: The influence of botanical source (waxy corn, glutinous rice, tapioca and potato), either based on crystallization or morphology, and the debranching time (6–48 h) on the physicochemical properties of debranched starches (DBSs) were systematically investigated. The divergence of depolymerization among different botanical sources within same hydrolysis time suggested that the debranching treatment was not only depending on the molecular profile and crystalline structure, but also related with the granular size and morphology of native starches. Fourier transformation infrared spectroscopy (FT-IR), X-ray diffraction (XRD), differential scanning calorimetry (DSC) suggested that long-term debranching reaction produced DBSs with improved degree of crystallization and reduced iodine binding capacity. Simulated in-vitro digestion assay showed that the proportion of digestive fractions from different botanical originated DBSs differed greatly. Additionally, prolonging the debranching time yielded increased level of resistant starch. The study may provide guidance for exploring DBSs with various molecular weight to fulfill their tailored applications.